Effect of plasma membrane monoamine transporter genetic variants on pharmacokinetics of metformin in humans - Moon, Seol Ju (Transl Clin Pharmacol, 2018)
Metformin, an oral hypoglycemic agent belonging to biguanide class, is widely used to treat type 2 diabetes mellitus, and several drug transporters such as organic cation transporters (OCTs), multidrug and toxin extrusion transporter (MATE), and plasma membrane monoamine transporter (PMAT) are thought to affect its disposition. We evaluated the role of PMAT genetic variations on the pharmacokinetic characteristics of metformin in a Korean population. In this retrospective study, 91 healthy subjects from four different metformin pharmacokinetic studies were analyzed; in each study, the subjects were administered two oral doses of metformin at intervals of 12 hours and dose-normalized pharmacokinetic parameters were compared between the subjects' genotypes. Subjects who had more than one allele of c.883-144A>G single nucleotide polymorphism (SNP) in PMAT gene (rs3889348) showed increased renal clearance of metformin compared to wild-type subjects (814.79 ± 391.73 vs. 619.90 ± 195.43 mL/min, p=0.003), whereas no differences in metformin exposure were observed between the PMAT variant subjects and wild-type subjects. Similarly, subjects with variant rs316019 SNP in OCT2 showed decreased renal clearance of metformin compared to wild-type subjects (586.01 ± 160.54 vs. 699.13 ± 291.40 mL/min, p=0.048). Other SNPs in PMAT and MATE1/2-K genes did not significantly affect metformin pharmacokinetics. In conclusion, the genetic variation of c.883-144A>G SNP in PMAT significantly affects the renal clearance of metformin in healthy Korean male subjects.